Perancangan Mebel Multifungsi Bermain Motorik untuk Kegunaan Pertumbuhan Balita di Rumah - Catherine Cynthia Kusuma (Intra, 2017)
Gaming is an activity that can be integrated in Early Childhood learning. The world of play is a colorful and fun world. Players will be comforted and happy to do so. From the word